Performing Participatory Citizenship – Politics and Power in Kerala's Kudumbashree Programme - Glyn Williams; Binitha V. Thampi; D. Narayana; Sailaja Nandigama & Dwaipayan Bhattacharyya
This article examines the operation of Kudumbashree, the Poverty Eradication Mission for the Indian State of Kerala. Kudumbashree operates through female-only Neighbourhood Groups, which aim to contribute to their participants’ economic uplift, and to integrate them with the activities and institutions of local governance. As such, Kudumbashree echoes poverty alleviation programmes elsewhere in the Global South designed to link poverty alleviation to ‘active citizenship’. This article evaluates the programme, looking in turn at its impacts on women’s participation in public space, its attempts to engineer participatory citizenship through engagement with the local state, and the wider consequences of its particular linking of participation and poverty alleviation for processes of exclusion within Kerala. It argues that although the programme has undoubtedly been successful in its scale and in supporting women’s public participation, questions remain over both the autonomy of the ‘invited spaces’ it has created, and the underlying vision of poverty alleviation it embodies.